2016
DOI: 10.3847/0067-0049/224/2/30
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Transients as a Source of Quasi-Periodic Processes in the Solar Atmosphere

Abstract: Solar dynamics and turbulence occur at all heights of the solar atmosphere and could be described as stochastic processes. We propose that finite lifetime transients recurring at a certain place could trigger quasi-periodic processes in the associated structures. In this study, we developed a mathematical model for finite lifetime and randomly occurring transients, and found that quasi-periodic processes, with period longer than the time scale of the transients, are detectable intrinsically in form of trains. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 98 publications
2
17
0
Order By: Relevance
“…The average spatial period is a few times longer than the correlation length L c , meaning that secondary waves need to traverse several correlation lengths before settling into a quasi-periodic signal. This is consistent with Yuan et al (2016). In addition, the temporal periodicity is found to be correlated with the spatial one, which is not surprising given that the fast wave pulse and secondary waves have an average speed of propagation of about unity in numerical units.…”
Section: Quasi-periodicity Of Secondary Wavessupporting
confidence: 88%
See 1 more Smart Citation
“…The average spatial period is a few times longer than the correlation length L c , meaning that secondary waves need to traverse several correlation lengths before settling into a quasi-periodic signal. This is consistent with Yuan et al (2016). In addition, the temporal periodicity is found to be correlated with the spatial one, which is not surprising given that the fast wave pulse and secondary waves have an average speed of propagation of about unity in numerical units.…”
Section: Quasi-periodicity Of Secondary Wavessupporting
confidence: 88%
“…The randomness in spatial structuring is transformed into the randomness in the temporal domain. As demonstrated in Yuan et al (2016), quasi-periodicity is an intrinsic property of a random time series, and the quasi-periods are usually a few times longer than the timescales of the transients.…”
Section: Quasi-periodicity Of Secondary Wavesmentioning
confidence: 99%
“…Recently, several authors have reported that small scale jets and spicules at transition region and chromosphere are associated with with PDs seen in polar plumes and polar coronal holes Jiao et al 2015;Samanta et al 2015;Bryans et al 2016;Yuan et al 2016). Reflections of propagating slow waves were also reported in hot and flaring coronal loops using AIA (Kumar et al 2013(Kumar et al , 2015 and XRT observations (Mandal et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Waves and oscillations are established within a sunspot, which act as a waveguide in response to the dynamics and turbulence of the solar interior (see a comprehensive review by Khomenko & Collados 2015). Analysis of the spatial and height distributions of the oscillations can reveal the magnetic (Reznikova & Shibasaki 2012;Yuan et al 2014b,a;Jess et al 2013Jess et al , 2016 and thermal structures of a sunspot (Zhugzhda 2008;Botha et al 2011;Snow et al 2015;Yuan et al 2016;Chae & Goode 2015;Kwak et al 2016). An isolated sunspot could be assumed to have an expanding axisymmetric magnetic field; inhomogeneities, such as light bridges, umbral dots, are normally observed at a variety of scales (see a review by Borrero & Ichimoto 2011).…”
Section: Introductionmentioning
confidence: 99%